Does remote COVID infection in pregnancy affect the placenta and pregnancy outcomes? – Results from a prospective cohort study (PLACENTA IN COVID/ PIC study) - N D Varunashree; Sherin Daniel; Swati Rathore; Mahesh Moorthy; Bijesh Yadav; Manisha M. Beck (Journal of Family Medicine and Primary Care)
Objectives: To study the rates of abnormal placentae and associated adverse perinatal outcomes in pregnant women who had COVID 19 infection during pregnancy, remote from delivery. To study the histopathological findings associated with these abnormal placentae. Methods: A prospective cohort study was carried out, recruiting pregnant women with singleton gestation, who had COVID 19 infection during their pregnancy, remote from delivery between August 2021 to July 2022. Ethics approval was obtained by the Institutional Review Board. Abnormal placentae were identified as those with weight <10th centile and associated histopathological findings were noted . Rates of SGA (small for gestational age) babies and stillbirths were recorded. The data was analyzed using Statistical Package for Social Sciences (SPSS) v 25. Results: Most of the 67 women in our cohort, had mild forms of COVID 19. Half had had infection in their second trimester. Among those infected in the third trimester, 93% were symptomatic. Gestational Diabetes was the most common associated medical condition. . Abnormal placentae were seen in 40%(n=27) of women. Half of these (15) were associated with SGA babies . Distribution of medical co morbidities was comparable among those with abnormal and healthy placentae. Most, 84%, SGA babies were born to mothers who had COVID <28 weeks GA. Conclusion: There is a small but significant risk of SGA babies being born to women who had COVID at<28 weeks, irrespective of medical comorbidities. Close monitoring of these pregnancies is, hence warranted.